Prevalence of dry eye in Bangkok, Thailand - Kaevalin Lekhanont (2018)
PURPOSE: To estimate the prevalence of dry eye in the adult population of Bangkok, Thailand. METHODS: Five hundred fifty volunteers 40 years of age or more who presented to the Ramathibodi Hospital for annual eye examinations were enrolled. Interviewers administered a dry eye symptoms questionnaire. Slit-lamp examination and objective dry eye assessment consisting of tear film breakup time (TBUT), fluorescein corneal staining, Schirmer tests, and meibomian gland evaluation were performed. Outcome measures included frequency of symptoms and positive dry eye tests. RESULTS: Thirty-four percent reported significant symptoms, which were defined as having one or more symptoms often or all of the time (95% confidence interval, 28.1-40.6). Approximately one half had meibomian gland disease (MGD) or pingueculum/pterygium (46.2 and 53.8%, respectively). Individuals with significant symptoms tended to be women (83.4%, P = 0.024), had MGD (63.6%, P = 0.006), had current artificial tear use (33.2%, P = 0.024), and had positive TBUT (80.7%, P = 0.000) and fluorescein staining (16.6%, P = 0.013.) The presence of pingueculum/pterygium and MGD were significantly associated with positive dry eye tests. CONCLUSION: This is the first report of prevalence of dry eye inclusive of signs and symptoms in an elderly Thai population. The prevalence of disease diagnosed on the basis of symptoms and dry eye tests was approximately 2 to 3 times higher than reported in whites. Women were more likely to report symptoms. Positive associations with dry eye tests were found in subjects with pingueculum/pterygium and MGD. © 2006 Lippincott Williams & Wilkins, Inc.